Papua New Guinea : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Papua New Guinea's economic activity has remained subdued in 2017. Slow growth, generous tax treatment of the Liquefied Natural Gas project, the drought and weak tax administration have all contributed to declining tax revenues and a substantial fiscal deficit and increasing debt-to-GDP ratio. Inflation was boosted to over 6 percent by drought effects, but is beginning to ease. Near-term risks to the outlook are tilted to the downside. Over the medium term, risks are more balanced owing to the upside potential of new resource sector projects and, possibly, a pickup in commodity export prices.